Enhancing Parental Participation in Government Schools: Overcoming Challenges and Promoting Active Participation - Katel, Niranjan; Katel, Krishna Prasad (Rabi Sangyan, 2024)
This study investigates the enhancement of parental engagement in government schools within the Solukhumbu district. The research aims to assess current levels of parental participation, identify key barriers, and propose effective strategies for improvement. Employing a qualitative research methodology, data were gathered through semi-structured interviews with twenty purposively selected head teachers from secondary schools. The analysis of the data yielded several critical findings. Geographical distance emerged as a significant obstacle to parental engagement, indicating a pressing need for virtual meetings and decentralized interactions to improve accessibility. Additionally, while parental involvement is robust within School Management Committees (SMCs), it tends to decline at the secondary education level. This trend underscores the necessity for tailored engagement strategies that cater specifically to the needs of older students and promote transparent communication between schools and parents. Furthermore, addressing barriers such as low parental literacy through targeted educational programs and enhancing communication channels is essential for fostering active parental engagement. The insights derived from this study provide valuable guidance for improving educational outcomes and nurturing a supportive learning environment in the government schools of Solukhumbu district.